Analysis of the Implementation of Environmental Accounting in Assessing Environmental Performance - Dewi Herawati, Shinta; Octavia, Evi; Rachmawati, Rima (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the implementation of environmental accounting in assessing environmental performance. The research method used in this research is descriptive analysis and is included in the type of library research. Based on the results of the study, it can be concluded that the implementation of environmental accounting has an impact on company performance, especially environmental performance. The company has an interest in improving environmental performance with the ultimate goal of increasing the profits it receives. One way to improve environmental performance is to implement environmental accounting in corporate accounting practices.